The crux of time: A meta-analysis of ex vivo whole blood degradation - Elliott, Colin I.; Shafer, Aaron B. A.; Stotesbury, Theresa E. (Frontiers in Analytical Science, 2022)
Estimating the time since deposition (TSD) of a bloodstain can provide important medico-legal information for crime scene investigation. Research in this area primarily investigates the degradation of either hemoglobin or genetic material over time. In this work, we present a comprehensive meta-analysis on bloodstain TSD research. Our results are interpreted from 25 quantitative studies used to probe the effect of biomolecule studied, analytical technique used, substrate porosity, environmental conditions, and blood source on TSD estimates. There was an overall strong effect of time across studies (Fisher’s Zr = 1.66, r = 0.93), and generally, we found that the type of biomolecule studied (e.g., hemoglobin, DNA) had equal effect sizes for TSD estimation. Differences in the mean TSD effect size were also observed between substrate porosity. Interestingly, the blood source does not significantly influence the magnitude of the effect sizes in TSD estimation. Despite the clear effect of time, forensically relevant prediction of bloodstain TSD remains complicated by inter-donor variability, type of substrate and environmental conditions. We recommend that future bloodstain TSD research increase sample size, include summary statistics and standardize experimental methodologies so that we can develop a quantitative understanding of the physicochemical processes involved in whole blood degradation in ex vivo conditions.